2021
DOI: 10.1002/qj.4108
|View full text |Cite
|
Sign up to set email alerts
|

Landfalling tropical cyclone characteristics and their multi‐timescale variability connected to monsoon and easterly formation environments over the western North Pacific

Abstract: This study analyses the impacts of tropical cyclones (TCs) that formed in monsoon and easterly environments on the major coastlines of the western North Pacific (WNP) basin during 1981–2009. The TC formation processes, defined as the development of tropical cloud cluster to TC, associated with monsoon environments (monsoon trough, monsoon confluence, and north of monsoon trough) are categorized into monsoon‐type TCs (monsoon‐TCs). Similarly, those associated with easterly flow environments (easterly flow west … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 122 publications
2
11
0
Order By: Relevance
“…Predicator two explains well the remote TCs, which is associated with the genesis‐related conditions in the central tropical Pacific and the steering flow to the north. Thus, we confirm that the three derived predictors represent three different genesis and track clusters of SCS TCs (e.g., Camargo et al., 2007; Chen et al., 2017; Kim & Seo, 2016; Teng et al., 2021).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Predicator two explains well the remote TCs, which is associated with the genesis‐related conditions in the central tropical Pacific and the steering flow to the north. Thus, we confirm that the three derived predictors represent three different genesis and track clusters of SCS TCs (e.g., Camargo et al., 2007; Chen et al., 2017; Kim & Seo, 2016; Teng et al., 2021).…”
Section: Resultssupporting
confidence: 80%
“…We anticipate plausible links between the MT and other predictors for PHL and SCS TCs (not described here). All these are consistent with the previous findings that a strengthening or an eastward shift of the MT encourages more TCs to form in the south-eastern sector of the basin, and a weakening or westward-shift of the MT favors more TCs to form in the western sector (Basconcillo et al, 2021;Chen et al, 2019;Molinari & Vollaro, 2013;Teng et al, 2021;Wu et al, 2012). The merit of the TC predictors is that they are not only associated with the genesis conditions (e.g., the MT) but also related to the background steering winds in which TCs are embedded.…”
Section: Phl Tc Predictorssupporting
confidence: 92%
See 2 more Smart Citations
“…Both Fu et al (2012) and Kerns and Chen (2013) suggested that the TC formation probability is more sensitive to the environmental dynamic conditions (e.g., low-level vorticity) for the WNP, while the thermodynamic conditions (e.g., water vapor content) appear to be more important for the North Atlantic. This is because TCs forming in the WNP are mostly associated with the monsoon system but associated with easterly waves in the North Atlantic (Teng et al 2019). However, given that TCs can also form under easterly conditions in the WNP, it is important to understand the contribution of each environmental parameter to TC formation separately for easterly-and monsoon-type TCs.…”
Section: Introductionmentioning
confidence: 99%